If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 9x + 6 + 4x = 4 + -1x + 2 Reorder the terms: 6 + 9x + 4x = 4 + -1x + 2 Combine like terms: 9x + 4x = 13x 6 + 13x = 4 + -1x + 2 Reorder the terms: 6 + 13x = 4 + 2 + -1x Combine like terms: 4 + 2 = 6 6 + 13x = 6 + -1x Add '-6' to each side of the equation. 6 + -6 + 13x = 6 + -6 + -1x Combine like terms: 6 + -6 = 0 0 + 13x = 6 + -6 + -1x 13x = 6 + -6 + -1x Combine like terms: 6 + -6 = 0 13x = 0 + -1x 13x = -1x Solving 13x = -1x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add 'x' to each side of the equation. 13x + x = -1x + x Combine like terms: 13x + x = 14x 14x = -1x + x Combine like terms: -1x + x = 0 14x = 0 Divide each side by '14'. x = 0 Simplifying x = 0
| 43=8x+3 | | 3(2t+1)-12=t-(t+8) | | x+23+4x=-32-4x-35 | | 3-24d-5=9d+18+1 | | 12=5-2x | | (-1)^(2/3) | | x+55=15 | | x+x+y+x+y= | | 5(3y+3)=6-3(y-3) | | (-1)^2/3 | | 5x+5(x+2)=20 | | -27-5r=-8r-48 | | -4.905x^2-22x+6=0 | | k+10*(-2)=5 | | -3(12+2k)=-(3k-6) | | 5(x+-6)+4=7(x+2)+-4 | | 1.15+0.8=2.3-1.5x | | 9x^2+18x-36=0 | | 3x/4-5/4=-5 | | 4(x+2)+b=2(x-3) | | 13/7-7/12 | | y=3(4)+25 | | 6x+12=p | | -x+1=3x-4x | | 11x+8=10(x+3)+5 | | 5x^3+25x^2= | | -5y+45=-10 | | -(7-2b)-6=-15 | | 2(3-4x)+1=-8 | | 2(-x+8)+3=2x+3 | | 12+3(x-4)-18=3[5-4(5-x)] | | sk-3(2k-3)=45 |